2019
DOI: 10.1101/850099
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain-Derived Extracellular Vesicles are Highly Enriched in the Prion Protein and Its C1 Fragment: Relevance for Cellular Uptake and Implications in Stroke

Abstract: Extracellular vesicles (EVs) are important means of intercellular communication and a potent tool for regenerative therapy. In ischemic stroke, transient blockage of a brain artery leads to a lack of glucose and oxygen in the affected brain tissue, provoking neuronal death by necrosis in the core of the ischemic region. The fate of neurons in the surrounding penumbra depends on the stimuli, including EVs, received during the following hours. A detailed characterization of such stimuli is crucial not only for u… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…PrP C is enriched in exosomes derived from a variety of cell types, including neural cells, and is also found in cerebral spinal fluid [ 74 ] and plasma [ 75 ]. Recent studies demonstrated that elevated levels of PrP C in extracellular vesicles (EVs)/exosomes may play a role in intercellular signaling and it is implicated in early stages after stroke [ 76 ]. Interestingly, the levels of PrP C in plasma exosomes of patients with Parkinson’s disease (PD) was directly correlated with cognitive impairment, suggesting a role for exosomal-PrP C in the prognosis of PD [ 77 ].…”
Section: Prp C In Intracellular Traffickingmentioning
confidence: 99%
“…PrP C is enriched in exosomes derived from a variety of cell types, including neural cells, and is also found in cerebral spinal fluid [ 74 ] and plasma [ 75 ]. Recent studies demonstrated that elevated levels of PrP C in extracellular vesicles (EVs)/exosomes may play a role in intercellular signaling and it is implicated in early stages after stroke [ 76 ]. Interestingly, the levels of PrP C in plasma exosomes of patients with Parkinson’s disease (PD) was directly correlated with cognitive impairment, suggesting a role for exosomal-PrP C in the prognosis of PD [ 77 ].…”
Section: Prp C In Intracellular Traffickingmentioning
confidence: 99%
“…PrPC is enriched in EVs [ 230 , 231 , 232 ] but not much is known about its physiological functions therein. We recently found that EVs purified from mouse brain are highly enriched in PrPC and its proteolytic C1 fragment (see paragraph above) [ 232 ]. PrP levels were further increased in EVs isolated from mice subjected to tMCAO (40 min) at 24 h after reperfusion.…”
Section: Another Way Of Releasing Information: Evs Prp and Its C1mentioning
confidence: 99%